A public health perspective on using electronic health records to address social determinants of health: The potential for a national system of local community health records in the United States. (April 2019) - Hatef, Elham; Weiner, Jonathan P.; Kharrazi, Hadi
Abstract: Community health records (CHRs) are defined as "a curated set of population-level indicators that describe the health and quality of life of a geographic community". CHRs encompass clinical, social determinants of health (SDOH), and public health data aggregated at the neighborhood level. If developed and deployed across communities, CHRs provide an opportunity to track and enhance population health on a regional or national level. Electronic Health Records (EHRs), if linked across providers, can document certain indicators of SDOH in addition to capturing clinical data for residents of a community. Moreover, EHR-derived patient-level SDOH information could be collated with geographic level public health and social services information to create the basis for neighborhood-specific CHRs. An EHR-derived CHR – relative to current survey-based assessments used by public health agencies in the United States and other countries – could dramatically increase the scope, quality, and timeliness of data available for planning interventions targeted at SDOH factors at both the consumer and small-area levels. EHR-derived CHRs, if assembled across neighborhoods, could also offer a significant value to the society by providing population-level SDOH data across various regions and eventually nationwide.